Optimalisasi Peran Baitul Mal Subulussalam Dalam Rangka Menurunkan Kemiskinan di Aceh - Koto, Amrizal (ITB AAS INDONESIA Surakarta, 2024)
Baitul Mal in Aceh is different from Baitul Mal in other provinces in Indonesia, where the Baitul Mal Subulusalam Institution is a functional institution while the secretariat is a structural institution that is directly responsible to the mayor. The aim of this research is to analyze the collection and distribution of zakat, infaq and alms funds from philanthropic institutions. The research method uses a qualitative design. The research object is the Baitul Mal Subulussalam institution in Aceh. The data collective conducted interviews with Baitul Mal Subulussalam administrators while data analysis used content analysis. The research results emphasize that the collection of zakat, infaq and alms funds at Baitul Mal Sulussalam comes from three sources. Firstly from the State Civil Apparatus and honorary staff who work in the Aceh Government, employees of state-owned enterprises and regional-owned enterprises in the province of Aceh. The two partners are working together on a government project worth IDR 50,000,000 (Fifty million rupiah). Third, zakat infaq and alms funds from the Muslim community in Aceh. Zakat is levied on employees from class three and above at 2.5% and employees who do not meet the requirements are subject to a 1% deduction from their salary. The collection of Zakat infaq and alms funds at Baitul mall Subulussalam in Aceh has not been implemented optimally even though it has been regulated by the Qonun that every State Civil Apparatus must pay zakat mall through salary deductions. There are still institutions in the government that have not paid zakat mal through Baitul Mal Subulussalam, such as the Republic of Indonesia Police and the National Army in Aceh. So the target for receiving zakat, infaq and alms funds has not yet reached the target. In 2022, the target of receiving zakat infaq and alms funds of twelve billion can only be realized at four point seven billion. The distribution of zakat infaq and alms funds has been carried out to eight eligible asnaf, except for the asnaf riqab, which does not exist. The most dominant distribution of zakat funds is given to Asnaf Fakir and Masakin. Productive zakat has been distributed to ultra-micro traders in order to improve the welfare of the people of Aceh. The distribution of infaq zakat funds and alms distributed for productive zakat is not followed up by providing business assistance.The effectiveness of the distribution of zakat infaq and alms funds at Baitul Mal Subulussalam cannot yet be measured in its success in reducing the poverty rate because the distribution of zakat infaq and alms funds in the form of productive zakat has not been followed up and assisted, so it cannot be measured to what extent the distribution of zakat infaq and alms funds has been succeeded in improving welfare in the form of mustahik turning into muzaki.